Using waveform modeling of seismic anisotropy to understand the process of Proterozoic lithospheric assembly - Solomon, Melinda A., author; Schutt, Derek L., advisor; Harry, Dennis, committee member; Hannah, Judy, committee member; Breidt, Jay, committee member (Colorado State University. Libraries, 2013)
In this study, SKS data from two long-standing broadband seismic stations located along the Proterozoic Trans Hudson Orogen is analyzed for the effects of complex anisotropy. The Trans Hudson Orogen is the lasting expression of collisional events that brought together Archean continental fragments to form the cratonic core of the North American continent. Split SKS waveforms observed at two GSN stations, FFC located on the Sask craton near Flin Flon, Manitoba, and RSSD located on the eastern margin of the Wyoming craton in the Black Hills of South Dakota, are analyzed for anisotropic layering of varying complexity. At FFC we find that a model with two flat layers of anisotropy is better able to explain the data than the simple model of one flat layer. A top layer shows anisotropy perpendicular to the convergence direction of the Trans Hudson Orogen that is similar to observations of anisotropy today at convergent margins, and is attributed to lithospheric deformation during convergence. RSSD shows more complex splitting that we interpret as sub-wavelength scale anisotropic heterogeneity resulting from convergence driven fragmentation of the pre-existing lithosphere into small, < ~40 km pieces. Previous studies show more coherent anisotropy to the east and west of RSSD, suggesting that anisotropic heterogeneity here is related to the convergence, and may be a longstanding feature of tectonic boundaries.
Keywords: anisotropy; SKS; seismology